Differential neutrophil responses in murine following intraperitoneal injections of Escherichia coli and Staphylococcus aureus - Yanyan Zhu; Jingya Luo; Xianzhu Xia; Hao Feng; Pingsen Zhao (Heliyon)
Objective: This study aimed to investigate the proportion of neutrophils among leukocytes, in various tissues following intraperitoneal injection of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) in mice. Methods: Twelve specific-pathogen free (SPF) male mice, aged eight weeks, were segregated into three groups, each containing four mice. Two of these groups were subjected to intraperitoneal injections of E. coli and S. aureus, both in high concentrations, to establish mouse models of inflammation. The remaining group, which received an intraperitoneal injection of phosphate buffered saline (PBS), served as the control group. Observe the mice every half hour. Then mice were anesthetized, and samples from peripheral blood, liver, and brain tissues were carefully collected nearing death. These samples underwent a digestion process to produce single-cell suspensions. Subsequently, these suspensions were stained with fluorescent antibodies targeting CD45, Ly6G, and CD11b. A flow cytometric analyzer was then employed to enumerate and compare the neutrophil alterations across each group (Fig. 1). Results: The results indicated a significant variation in the ratio of CD11b+ Ly6G+ neutrophils to CD45+ leukocytes among the groups. In peripheral blood, the control group showed a neutrophil proportion of approximately 1.44 %, while the E. coli and S. aureus groups exhibited increased proportions of 6.53 % and 3.82 %, respectively. In liver tissue, a marked elevation was observed in the experimental groups, with ratios of 19.20 % and 20.40 % for E. coli and S. aureus, respectively, compared to 1.64 % in the control. In brain tissue, the increments were more modest but noticeable, with the experimental groups showing 2.40 % and 1.11 % in contrast to 0.13 % in the control group. Conclusions: These findings suggest neutrophils are involved in the response after intraperitoneal injection of E. coli and S. aureus, with marked differences in neutrophil responses in different tissues. This study enhances our understanding of the acute inflammatory response to bacterial infection.